Phase-dependent strategy to mimic quantum phase transitions - Zhou, Yuan; Cao, Lian-Zhen; Wang, Qing-Lan; Hu, Chang-Sheng; Zhang, Zhu-Cheng; Xiong, Wei (Frontiers in Quantum Science and Technology, 2023)
This study proposes a hybrid quantum system of an ensemble of collective spins coupled to a surface acoustic wave (SAW) cavity through a sideband design. Assisted by a dichromatic optical drive with a phase-dependent control, this spin ensemble can effectively mimic different types of long-range Lipkin–Meshkov–Glick (LMG) interactions and then undergo quantum phase transitions (QPTs) due to phase-induced spontaneous symmetry breaking (SSB). In addition, this phase-controlled scheme also ensures the dynamical preparation of the spin-squeezed state (SSS), which may be a useful application in quantum measurement. This study is a fresh attempt at quantum manipulation based on acoustic control and also provides a promising route toward useful applications in quantum information processing, especially the adiabatic preparation of multiparticle-entangled ground states via QPTs; i.e., the Greenberger–Horne–Zeilinger (GHZ) or W-type states.